Legal Analysis of Financial Technology (Fintech) Based Online Loan Agreements and The Legal Consequences - Yovan Raphael S. Pandia; Widodo Ramadhana (Journal Equity of Law and Governance, 2025)
Borrowing and lending activities, whether conducted directly or indirectly, have become an integral part of people's lives, particularly with the rise of Financial Technology (Fintech). Fintech refers to financial services leveraging advancements in computerized technology to facilitate transactions, making it easier for individuals to conduct transactions involving products, goods, and services. Against this backdrop, this study explores key issues related to fintech-based online loan agreements: (1) What is the mechanism for canceling a fintech online loan agreement under applicable laws? (2) What forms of legal protection are available for debtors entering into fintech-based online loan agreements? (3) What are the legal consequences of canceling such agreements for both lenders and borrowers? This study employs a normative legal research method, collecting data from primary and secondary legal materials, including journals, literature, and statutory regulations. The collected materials are analyzed qualitatively and descriptively. The findings reveal that fintech-based online loan agreements may be invalidated if they fail to meet the requirements outlined in Article 1320 of the Civil Code or violate Article 47 paragraph (2) of Government Regulation Number 82 of 2012 concerning the Implementation of Electronic Systems and Transactions (PP PSTE). Furthermore, legal protection for creditors in fintech-based agreements comprises both preventive measures and repressive legal protections.